The Jurisprudence of Balancing in International Relations: Applied Models (Raparin Journal of Humanities (RJH), 2026)
In this study, entitled “The Jurisprudence of Balancing in International Relations: Applied Models, the researcher examines the jurisprudence of balancing (Fiqh al-Muwazanat), as an independent science within Islamic jurisprudence. The study includes a definition of this field, then outlines the various types of balancing. And substantiates its legitimacy with evidence derived from the Qur’an, the Sunnah, scholarly consensus, and rational deduction, The study also highlights the dispersed contributions of classical scholars in this field, the researcher outlines the necessary regulations and criteria for applying, particularly in weighing benefitsand harms and explains the significance of balancing conflicting interests and how to prioritize between them in cases of contradiction.Then the researcher explains the subject of international relations in Islam. It includes the definition of Ilm al-Siyar (Biography) according to ancient scholars and the concept of international relations among contemporaries.he examines the foundation of international relations in Islamic jurisprudence, drawing on evidence from the Qur’an, the Sunnah, events from the biography of Muhammad(ﷺ), the actions of the Rashidun Caliphs, and Islamic history, and he refers to the stages of development of international relations among scholars, and the researcher explains the distinct characteristics of Islamic international relations, which are characterized by a set of values and principles that distinguish it from others.Finally, the researcher presents practical models demonstrating the process of balancing benefits and harms in matters pertaining to international relations, and explains how to balance interests and harms in these models, and how to weigh up if they conflict.